2012
DOI: 10.1007/s10709-012-9693-2
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic chromosome pairing in Actinidia chinensis var. deliciosa

Abstract: Polyploids are defined as either autopolyploids or allopolyploids, depending on their mode of origin and/or chromosome pairing behaviour. Autopolyploids have chromosome sets that are the result of the duplication or combination of related genomes (e.g., AAAA), while allopolyploids result from the combination of sets of chromosomes from two or more different taxa (e.g., AABB, AABBCC). Allopolyploids are expected to show preferential pairing of homologous chromosomes from within each parental sub-genome, leading… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Non-preferential chromosome pairing occurs during meiosis when chromosomes pair with more than one potential homologue partner. Both natural and induced polyploids in kiwifruit can form multivalent chromosome formations (Mertten et al 2012 ; Wu et al 2014 ). This finding suggests an adjustment of NRM to polyploidy, and double reduction (ω) should be considered in the breeding strategy of Actinidia spp.…”
Section: Introductionmentioning
confidence: 99%
“…Non-preferential chromosome pairing occurs during meiosis when chromosomes pair with more than one potential homologue partner. Both natural and induced polyploids in kiwifruit can form multivalent chromosome formations (Mertten et al 2012 ; Wu et al 2014 ). This finding suggests an adjustment of NRM to polyploidy, and double reduction (ω) should be considered in the breeding strategy of Actinidia spp.…”
Section: Introductionmentioning
confidence: 99%
“…Crowhurst and Gardner (1991) suggested that A. deliciosa may be an allopolyploid species with diploid A. chinense as one parent; A. deliciosa has a family of repeat sequences that is absent in diploid A. chinensis , but the other parental species is (are) unknown. However, the absence of preferential chromosome pairing suggests that A. deliciosa is an autopolyploid species in terms of chromosome behaviour (Mertten et al., 2012). Analyses of isozyme polymorphisms also support an autopolyploid origin (Testolin & Ferguso, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…So, by elucidating the genetic variations in triploid loquats after their formation, more details could be provided for elucidating the above phenomenon (heterosis) in triploid loquats as well as triploid loquat breeding. However, it is quite hard for us to carry out relative research on the genetic variations in triploid loquats due to the fact that the origin and evolution of loquats are still unclear, which makes it impossible for us to conduct a study using natural triploid loquats, whereas cross-breeding provides us with an effective solution to this problem since tetraploid loquats have limited fertility, based on reported studies, and the egg cells of tetraploid loquats produced via megaspore-mother-cell meiosis contain a certain number of viable diploid egg cells, which could be fertilized by the diploid father [ 39 ]. Based on this, Wang (2008) successfully obtained several triploid loquats via cross-breeding (4× × 2×) and analyzed their genetic variations after their formation using the AFLP marker [ 40 ].…”
Section: Introductionmentioning
confidence: 99%